橄榄油对急性胃黏膜损伤的保护作用及机制研究Protective effect of olive oil on acute gastric mucosal injury and its mechanism - 陈燕玲，杨瑞，赵声兰 CHEN Yanling, YANG Rui, ZHAO Shenglan (Zhongguo youzhi, 2025)
旨在为橄榄油的功能扩展和高值化开发利用提供依据，通过给小鼠灌胃高浓度乙醇建立急性胃黏膜损伤模型，研究摄入不同剂量橄榄油对小鼠急性胃黏膜损伤的保护作用，并通过对小鼠血清及胃组织中相关因子的变化及橄榄油剂量与胃黏膜损伤抑制率及上述因子的相关性分析探讨其作用机制。结果表明：与模型组相比，橄榄油高（8.0 mL/kg）、中（4.0 mL/kg）、低（2.0 mL/kg）剂量组均能有效降低小鼠急性胃黏膜损伤，小鼠胃组织仅见少量出血点和溃疡，胃黏膜损伤指数显著降低，胃黏膜损伤抑制率分别为60.58%、52.28%、46.06%；橄榄油各剂量组均能改善小鼠胃黏膜上皮细胞脱落、充血及胃腺坏死情况，病理损伤积分均显著降低，橄榄油各剂量组小鼠胃组织中超氧化物歧化酶（SOD）活力、前列腺素E2（PGE2）含量和B淋巴细胞瘤-2（Bcl-2）mRNA转录水平均显著提高，血清中白细胞介素-6（IL-6）、肿瘤坏死因子-α（TNF-α）、白细胞介素-1β（IL-1β）含量及胃组织中丙二醛（MDA）含量、核转录因子-κB（NF-κB）和Bcl-2相关X蛋白（Bax） mRNA转录水平均显著降低；相关性分析结果表明橄榄油剂量与胃黏膜损伤抑制率、胃组织中SOD活力、PGE2含量和Bcl-2 mRNA转录水平均呈显著正相关，与血清中IL-6、TNF-α、IL-1β含量及胃组织中MDA含量、胃组织中NF-κB和Bax mRNA转录水平呈显著负相关。综上，橄榄油可能通过抑制炎症反应，降低氧化应激水平，增强胃黏膜屏障和修复功能，调节NF-κB、Bcl-2和Bax mRNA的转录水平，对乙醇诱导的急性胃黏膜损伤发挥保护作用。 In order to provide a basis for the functional expansion and high-value development and utilization of olive oil, acute gastric mucosal injury model was established in mice by intragastric administration of high concentration ethanol. The protective effects of different doses of olive oil on acute gastric mucosal injury in mice were investigated, and the underlying mechanisms were explored through analysis of relevant factors in serum and gastric tissues and the correlation between olive oil dosage, injury inhibition rate, and the relevant factors. The results showed that compared with the model group, olive oil high (8.0 mL/kg), medium (4.0 mL/kg) and low (2.0 mL/kg) dose groups could effectively reduce the acute gastric mucosal injury in mice, and only a small amount of bleeding spots and ulcers in gastric tissue of mice were observed. The gastric mucosal injury index significantly decreased, and the injury inhibition rates of olive oil high, medium and low dose groups were 60.58%, 52.28%, and 46.06%, respectively. Olive oil in all dose groups could improve gastric mucosal epithelial cell shedding, mucosal congestion, and gastric gland necrosis in mice, with significantly reduced pathological damage scores. The activity of superoxide dismutase (SOD), the content of prostaglandin E2 (PGE2), and the mRNA transcription level of B-cell lymphoma-2 (Bcl-2) in gastric tissue of mice in each olive oil dose group increased significantly. The contents of interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and interleukin-1β (IL-1β) in serum, malondialdehyde (MDA) content and the mRNA transcription levels of nuclear factor-κB (NF-κB) and Bcl-2-associated X protein (Bax) in gastric tissue of mice decreased significantly. Pearson correlation analysis showed that the dose of olive oil was significantly positively correlated with the injury inhibition rate of gastric mucosal, the contents of SOD and PGE2 in gastric tissue, and the mRNA transcription level of Bcl-2, and significantly negatively correlated with the levels of IL-6, TNF-α, IL-1β in serum, MDA content in gastric tissue, and mRNA transcription levels of NF-κB and Bax in gastric tissue. In conclusion, olive oil may play a protective role in acute gastric mucosal injury induced by ethanol by inhibiting inflammatory response, reducing oxidative stress level, enhancing gastric mucosal barrier and repair function, regulating the transcription levels of NF-κB, Bcl-2 and Bax mRNA.